Donald Barthelme : An Exhibition - Klinkowitz, Jerome (Book collections on Project MUSE., 1991)
Donald Barthelme (1931-1989) is regarded as one of the most imitated and influential American fiction writers since the early 1960s. In Donald Barthelme: An Exhibition, Jerome Klinkowitz presents both an appreciation and a comprehensive examination of the life work of this pathbreaking contemporary writer. A blend of close reading, biography, and theory, this retrospective-informed by Klinkowitz's expert command of postmodern American fiction-contributes significantly to a new understanding of Barthelme's work. Klinkowitz argues that the central piece in the Barthelme canon, and the key to his.